The role of ultrasound in first-trimester screening after the introduction of NIPT as a service of public health insurance – a consensus statement of the Fetal Medicine Foundation (FMF) Germany - Merz, Eberhard; Eiben, Bernd; Thode, Christian; Hackelöer, Bernhard-Joachim; Faber, Renaldo; Tercanli, Sevgi; Alkier, Rudolf (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Combined first-trimester screening (FTS) and noninvasive prenatal testing (NIPT) have been proven to be reliable noninvasive procedures to detect the most common chromosomal abnormalities (trisomies 21, 18, 13) in the first trimester. The aim of this paper is to demonstrate the strengths and limitations of these two procedures and to give a consensus statement of the Fetal Medicine Foundation (FMF) Germany on how to use the two techniques in the first trimester after the introduction of NIPT as a service of the statutory health insurance companies in Germany.
Keywords: Combined first-trimester screening; contingent screening; cell-free fetal DNA; prenatal ultrasound; chromosome anomalies